Peran Psikologi Hukum dalam Permasalahan Anak Berhadapan dengan Hukum - Melisa Dwi Fransiska; Andhiyah Ivena Ramadani; Dominikus Rato; Fendi Setyawan (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Within the child there is inherent dignity and rights as a human embodiment that must be upheld. Therefore, it will create Indonesian children who are prosperous, high quality and have noble character. The existence of indiscipline towards legal norms that apply in society results in juvenile delinquency. Legal psychology here plays a very important role in the balance between legal and psychological norms for children. The purpose of this research is to find out about children in conflict with the law, the problems that occur with children in conflict with the law and the role of legal psychology in the future in the mental and psychological balance of children and the legal norms that exist in society. The methodology used is a normative juridical approach. So this research comes to the conclusion that the form of handling children in conflict with the law requires a legal approach based on legal psychology to provide a reference and the causes of violations that occur to children can be analyzed.